CONNECTING THE VANISHING FLORA, FAUNA AND ITS RELATION TO THE INDIAN REMOVAL POLICY AS SEEN IN COOPERS THE LEATHERSTOCKING TALES - Ceisy Nita Wuntu (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
This study aims at connecting the vanishing flora, fauna and its Relation to the Indian removal policy in Coopers The Leatherstocking Tales. This research applies an American Studies interdisciplinary principle supplemented by the myth and symbol theory proposed by Henry Nash Smith. Smith claimed the importance of imaginative works in revealing American culture. He declared that the historical, anthropological and cultural, sociological, and ecological data as covered in this research can be equipped by data from imaginative works. Hence, in this research, those data are presented integratedly in their context of past and present. In this research, in order to highlight environmental matters in Coopers The Leatherstocking Tales, the analysis covers the data above that are integrated with the data revealed in The Leatherstocking Tales as a whole by employing the concept of ecocriticism. The spirit of the immigrants to have a better life in the new world, stimulated by its rich, lush and beautiful circumstances, in fact, is not an aim of a sustainable life. The desire to improve their life is not enough without using and treating its environment wisely as well as facing it with the environmental conservation paradigm. The spirit of doing the exploitation is a consequence of western humanism value. The reason of coming to America to avoid the population density as well as the competition of life cannot be attained when the immigrants experience the same population density and harsh competition as in their old world and when the beautiful nature disappears, the forests become cities, the tranquility becomes noisy and crowded, and the people experience the uncomfortable life that many kinds of conflict can follow. It is not on the right path when they cannot maintain the grandeur of nature, because they are not directing their way to the right, sustainable way of life as alerted and meant by Cooper. Ecologically, the superabundance of the land when it was encountered by the European immigrants had been a factor that had made the American people arrogant with the environment. The damage of the environment that is understood anthropologically, culturally, sociologically and ecologically was not an individual mistake. It was the responsibility of the government to provide law enforcement but unfortunately the government got involved in the violation of human rights and of the activities of exploiting natural resources. To Cooper, as seen in his work, the spirit of exploiting life and the environment can be overcome by the moral of ecological awareness. It is a hierarchy that starts from love or compassion, then appreciation, respect, wisdom, and justice and this hierarchy should be assisted by law. Coopers ecological moral awareness arose as a protest against American progress. The immigrants progress to Cooper is an extermination of human, flora, and fauna.